Efficient authentication scheme for double-layer satellite network - Hui ZHU; Heng WU; Haiqiang ZHAO; Yuqing ZHAO; Hui LI (Tongxin xuebao)
To solve the issue of networking authentication among GEO and LEO satellites in double-layer satellite network,a secure and efficient authenticated key agreement scheme was proposed.Based on symmetric encryption,the proposed scheme can achieve trust establishment and secure communication between satellites without the trusted third party.Meanwhile,considering characteristics of highly unified clock and predictable satellite trajectory in satellite networks,a pre-calculation method was designed,which can effectively improve the authentication efficiency of satellite networking.Moreover,formal proof and security analysis demonstrate that the scheme can satisfy various security requirements during satellite networking.Performance analysis and simulation results show that the scheme has low computation and communication overhead,which can achieve the authentication of satellite networking in resource-limited scenarios.